2018
DOI: 10.1155/2018/1023025
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin‐1 Protects Bone Marrow‐Derived Mesenchymal Stromal Cells from Hyperoxia‐Induced Injury In Vitro

Abstract: Background The poor survival rate of mesenchymal stromal cells (MSC) transplanted into recipient lungs greatly limits their therapeutic efficacy for diseases like bronchopulmonary dysplasia (BPD). The aim of this study is to evaluate the effect of thioredoxin-1 (Trx-1) overexpression on improving the potential for bone marrow-derived mesenchymal stromal cells (BMSCs) to confer resistance against hyperoxia-induced cell injury. Methods 80% O2 was used to imitate the microenvironment surrounding-transplanted cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Zhang et al. ( 2018 ) reported that high glucose caused a time-dependent decrease in the expression of PGC-1α, NRF1 and TFAM in mouse podocytes, and an increase in ROS levels in cells and mitochondria. The study by Nanjaiah and Vallikannan ( 2019 ) revealed that hyperglycaemia affected mitochondria in the retina, and diminished mitochondrial biogenesis by downregulation of PGC-1α and TFAM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al. ( 2018 ) reported that high glucose caused a time-dependent decrease in the expression of PGC-1α, NRF1 and TFAM in mouse podocytes, and an increase in ROS levels in cells and mitochondria. The study by Nanjaiah and Vallikannan ( 2019 ) revealed that hyperglycaemia affected mitochondria in the retina, and diminished mitochondrial biogenesis by downregulation of PGC-1α and TFAM.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia causes overexpression of TXNIP, which interacts with TRX1 and inhibits its nuclear translocation, thus blocking TRX1-dependent gene transcription and the expression of genes associated with cell death and survival (Dunn et al 2010). Zhang et al (2018) reported that high glucose caused a time-dependent decrease in the expression of PGC-1a, NRF1 and TFAM in mouse podocytes, and an increase in ROS levels in cells and mitochondria. The study by Nanjaiah and Vallikannan (2019) revealed that hyperglycaemia affected mitochondria in the retina, and diminished mitochondrial biogenesis by downregulation of PGC-1a and TFAM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize lung injury in the BPD model, the antioxidant capacity of the TXN system is dependent on the activation of Nrf2 and an increase in lung epithelial HO-1 expression ( 69 ). According to Zhang et al, TXN1 overexpression reduced apoptosis and increased MSC proliferation in lung MSCs transplanted into recipients, SOD levels, and GPX levels ( 70 ). TXN1 is a new target for BPD treatment in neonatal lung disorders as it is resistant to hyperoxic lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…On a similar note, many of the critical enzymes involved in glutathione synthesis, as well as phase, I, II, and III xenobiotic/drug metabolism are regulated by NRF2 ( Dodson et al, 2019 ). Accordingly, high levels of glutathione have been shown to be required for MSC function, and increased expression of the catalytic and modulatory subunits of glutamate cysteine ligase (GCLC/GCLM), glutathione reductase (GR), and thioredoxin-1 (TXN1) have all been associated with the increased ability of MSCs to self-renew, migrate, and mitigate the effects of pro-inflammatory stimuli/oxidative insult, particularly when transplanted as a form of immunotherapy ( Jeong et al, 2018 ; Zhang et al, 2018 ; Lim et al, 2020 ). High glutathione and glutathione peroxidase 2 (GPX2) levels have also been reported in iPSCs, with depletion of GPX2 resulting in increased ROS-dependent DNA damage ( Dannenmann et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%